Selective hydrogenation of halogenated arenes using porous manganese oxide (OMS-2) and platinum supported OMS-2 catalysts. (20th April 2016) - McManus, Iain J.; Daly, Helen; Manyar, Haresh G.; Taylor, S. F. Rebecca; Thompson, Jillian M.; Hardacre, Christopher
Abstract : Porous manganese oxide (OMS-2) and platinum supported on OMS-2 catalysts have been shown to facilitate the hydrogenation of the nitro group in chloronitrobenzene to give chloroaniline with no dehalogenation. Complete conversion was obtained within 2 h at 25 °C and, although the rate of reaction increased with increasing temperature up to 100 °C, the selectivity to chloroaniline remained at 99.0%. Use of Pd/OMS-2 or Pt/Al2 O3 resulted in significant dechlorination even at 25 °C and 2 bar hydrogen pressure giving a selectivity to chloroaniline of 34.5% and 77.8%, respectively, at complete conversion. This demonstrates the potential of using platinum group metal free catalysts for the selective hydrogenation of halogenated aromatics. Two pathways were observed for the analogous nitrobenzene hydrogenation depending on the catalyst used. The hydrogenation of nitrobenzene was found to follow a direct pathway to aniline and nitrosobenzene over Pd/OMS-2 in contrast to the OMS and Pt/OMS-2 catalysts which resulted in formation of nitrosobenzene, azoxybenzene and azobenzene/hydrazobenzene intermediates before complete conversion to aniline. These results indicate that for Pt/OMS-2 the hydrogenation proceeds predominantly over the support with the metal acting to dissociate hydrogen. In the case of Pd/OMS-2 both the hydrogenation and hydrogen adsorption occur on the metal sites.